Application of effective microorganisms technology on management and meat quality of japanese quail - Mohd. Fadzal, Mohd. Fadzli (2007)
To investigate the management and meat quality To investigate the management and meat quality of the Japanese Quail ( of the Japanese Quail (Coturnix Coturnix Japonica Japonica) following the application of following the application of Effective Microorganisms technology.